2018
DOI: 10.1182/bloodadvances.2018021758
|View full text |Cite
|
Sign up to set email alerts
|

The endogenous antimicrobial cathelicidin LL37 induces platelet activation and augments thrombus formation

Abstract: Platelet-associated complications including thrombosis, thrombocytopenia, and hemorrhage are commonly observed during various inflammatory diseases such as sepsis, inflammatory bowel disease, and psoriasis. Despite the reported evidence on numerous mechanisms/molecules that may contribute to the dysfunction of platelets, the primary mechanisms that underpin platelet-associated complications during inflammatory diseases are not fully established. Here, we report the discovery of formyl peptide receptor 2, FPR2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 53 publications
7
56
0
Order By: Relevance
“…Notably, the activation of platelets using 1 μg/mL cross‐linked collagen‐related peptide (CRP‐XL) increased the level of FPR1 on the surface as determined by flow cytometry (Figure AI), while the level of proteins identified by immunoblots remained unchanged (Figure AII). These data confirm the presence of FPR1 in platelets, possibly in granules or the open canalicular system or both, and their increase on the surface upon activation similar to FPR2/ALX …”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Notably, the activation of platelets using 1 μg/mL cross‐linked collagen‐related peptide (CRP‐XL) increased the level of FPR1 on the surface as determined by flow cytometry (Figure AI), while the level of proteins identified by immunoblots remained unchanged (Figure AII). These data confirm the presence of FPR1 in platelets, possibly in granules or the open canalicular system or both, and their increase on the surface upon activation similar to FPR2/ALX …”
Section: Resultssupporting
confidence: 80%
“…Recently, we have reported the presence of FPR2/ALX in human and its orthologue, Fpr2/3 in human platelets . Similarly, the expression of FPR1 in human platelets at protein level, and in megakaryocytes at transcript level, has been previously reported .…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…The antimicrobial peptide cathelicidin (CRAMP in mouse/rat, LL-37 in human) is expressed in many immune cells, such as epithelial cells, and genital cells 10 . CRAMP was initially reported as an immunomodulatory peptide that functions in many autoimmune diseases, such as psoriasis 11 , systemic lupus erythematous 12 , arthritis 13 , atherosclerosis 14 , and type 1 diabetes 15 . Recent studies have identified a role of CRAMP in cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…In an open wound, the LL37 contained within the granules of platelets is released to the local environment to support microbial clearance, activate the inflammatory response and modulate thrombosis and hemostasis. Reports have shown LL37 to promote thrombus formation, reduce the clotting time (in mice tails) and, generally, accelerate healing . The mechanisms by which LL37 intervenes in the coagulation cascade are still under investigation; however, it is clear that its presence within neutrophils, monocytes, and platelets to be extremely important during this process.…”
Section: Resultsmentioning
confidence: 99%